2012
DOI: 10.1002/pen.23389
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of electrospinning of poly(caprolactone) via a multi‐nozzle spinneret connected to a twin screw extruder and properties of electrospun fibers

Abstract: Conventional electrospinning is a simple process, suitable for the processing of solvated polymers at relatively low rates. It lacks the capabilities of conveying of solids, mixing of polymeric resins and devolatilization and has limited capabilities in melting and incorporation of fillers, including nanoparticles. The use of a twin screw extruder as the front end of the electrospinning process provides these capabilities but only becomes feasible at relatively high throughput rates. Such high rates of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Electrospinning has also been combined with traditional polymer processing techniques such as twin-screw extrusion in order to improve the ability to spin more viscous systems including polymer melts [60]. Moreover, such a process can generate high production rates when combined with multi-nozzle spinnerets ( Figure 7b) [61]. Recently also alternative spinning technologies for nanofibers have been introduced, such as a rotary jet-spinning technology that is capable of high rate spinning [62].…”
Section: Solution Jetmentioning
confidence: 99%
“…Electrospinning has also been combined with traditional polymer processing techniques such as twin-screw extrusion in order to improve the ability to spin more viscous systems including polymer melts [60]. Moreover, such a process can generate high production rates when combined with multi-nozzle spinnerets ( Figure 7b) [61]. Recently also alternative spinning technologies for nanofibers have been introduced, such as a rotary jet-spinning technology that is capable of high rate spinning [62].…”
Section: Solution Jetmentioning
confidence: 99%
“…[47,48]. Concentration of actin on the cell periphery and at cell-cell junctions reveal that PCL and PCL/collagen nanofibrous scaffolds support cellular interactions among keratinocytes and direct them for the formation of strong cell sheets required for wound healing and epidermal tissue engineering [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…However, some efforts are being focused on integrating the electrospinning method into continuous industrial processes. In the field of plastics engineering, the work of Senturk‐Ozer et al recently demonstrated the use of a twin‐screw extruder (TSE) as the front end of the electrospinning process. For this, high rates of electrospun jets were absolutely necessary and those could only be achieved by using multi‐nozzle spinnerets.…”
Section: Conclusion and Industrial Bioactive Applications For The Elmentioning
confidence: 99%